2003
DOI: 10.3989/scimar.2003.67n113
|View full text |Cite
|
Sign up to set email alerts
|

Larval condition and growth of <i>Sardinella brasiliensis </i> (Steindachner, 1879): preliminary results from laboratory studies

Abstract: SUMMARY: Brazilian sardine, the most important resource along the southeastern Brazilian coast, presented great variations and declines in its stocks. The main factors contributing to this are: oceanographic structure changes; recruitment failures; excessive catches of juveniles and increase in fishery effort. In spite of this, no alterations in the density-dependent parameters were detected. Consequently, methods analysing the condition of the larvae coupled with methods determining growth using sagittae otol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…In marine fish larvae, pancreatic and intestinal enzymes are generally low at first feeding and in some species are even not detected (Kolkovski, 2001). Previous studies of Brazilian sardine larvae also showed low levels of tryptic enzyme activity at a similar age and development stage (Bianco Rossi-Wongtschowski et al, 2003;Dias et al, 2004). Therefore, it is necessary to use more sensitive methods to clarify protease activity in Brazilian sardine larvae.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In marine fish larvae, pancreatic and intestinal enzymes are generally low at first feeding and in some species are even not detected (Kolkovski, 2001). Previous studies of Brazilian sardine larvae also showed low levels of tryptic enzyme activity at a similar age and development stage (Bianco Rossi-Wongtschowski et al, 2003;Dias et al, 2004). Therefore, it is necessary to use more sensitive methods to clarify protease activity in Brazilian sardine larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The use of microalgae in marine fish hatcheries is interesting from an economic, nutritional and environmental perspective (Benetti et al, 2008;Nielsen et al, 2017). One positive effect of the green water technique is the stability of the water (Conceição et al, 2010;Naas & Harboe, 1992), since microalgae release oxygen and consume nitrogen compounds (Muller-Feuga, 2000;Shan & Lin, 2014). To reduce costs, alternative products, such as preserved microalgae, have been proposed to replace live microalgae in marine aquaculture (Nielsen et al, 2017;Richmond & Hu, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations